Readdressing the question of how “Islamic” Islamic banks are: the dependency of Islamic bank rates on conventional rates and the impact of monetary policy - Mohamed Saeed, Shifa (2019)
Purpose – This paper aims to determine the relationship between Islamic bank rates and their conventional counterparts when monetary-policy-rates are included in the analysis. Hence, the paper aims to explain why there is a relationship between the Islamic bank rates and conventional-bank rates.